The Role of Hypertext in Consumer Decision Making. The Case of Travel Destination Choice - Raúl Valdez Munoz (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Travel is one of the most popular items people tend to be comfortable with purchasing over the Internet. Hypertext is a form of electronic text composed of blocks of words (or images) linked electronically by multiple paths, chains, or trails. This study explores the importance of hypertext in the travel destination choice from websites. Results show that hypertext links containing images of destinations, informative texts, and search tools are the three most important features utilized by tourist website browsers. This study aims to offer insights into new areas for further research on tourism websites design, application and evaluation.